Hybrid macrocycle formation and spiro annulation on cis-syn-cis-tricyclo[6.3.0.02,6]undeca-3,11-dione and its congeners via ring-closing metathesis - Kotha, Sambasivarao; Chinnam, Ajay Kumar; Ali, Rashid (Beilstein Journal of Organic Chemistry, 2015)
We have developed a simple methodology to transform cis-syn-cis-triquinane derivative 2 into the diindole based macrocycle 6 involving Fischer indolization and ring-closing metathesis (RCM). Various spiro-polyquinane derivatives have been assembled via RCM as a key step.
Keywords: aza-polyquiananes; Fischer indolization; macrocycles; ring-closing metathesis; spiropolyquinanes

Strained Organic Molecules - Greenberg, A.; Liebman, J. F. (Academic Press, 1978)

Cage Hydrocarbons - Olah, G. A. (John-Wiley, 1990)

Fascinating Molecules in Organic Chemistry - Vögtle, F. (Wiley, 1992)

Carbocyclic Cage Compounds: Chemistry and Applications - Ōsawa, E.; Yonemitsu, O. (VCH, 1992)

Classics in Hydrocarbon Chemistry - Hopf, H. (Wiley-VCH, 2000)

(untitled) - Mehta, G.; Srikrishna, A. (Chem. Rev., 1997)

(untitled) - Wender, P. A.; Dore, T. M.; deLong, M. A. (Tetrahedron Lett., 1996)

(untitled) - Tzvetkov, N. T.; Neumann, B.; Stammler, H.-G.; Mattay, J. (Eur. J. Org. Chem., 2006)

(untitled) - Camps, P.; Fernández, J. A.; Vázquez, S. (ARKIVOC, 2010)

Polyquinane Chemistry, Synthesis and Reactions - Paquette, L. A.; Doherty, A. M. (Springer-Verlag, 1987)

(untitled) - Ramaiah, M. (Synthesis, 1984)

(untitled) - Singh, V.; Thomas, B. (Tetrahedron, 1998)

(untitled) - Toyota, M.; Nishikawa, Y.; Motoki, K.; Yoshida, N.; Fukumoto, K. (Tetrahedron, 1993)

(untitled) - Liao, C.-C. (Pure Appl. Chem., 2005)

(untitled) - Srikrishna, A.; Dethe, D. H. (Indian J. Chem., 2011)

(untitled) - Tolstikov, G. A.; Ismailov, S. A.; Gimalova, F. A.; Ivanova, N. A.; Miftakhov, M. S. (Russ. Chem. Bull., 2013)

(untitled) - Heasley, B. (Curr. Org. Chem., 2014)

(untitled) - Chaplin, J. H.; Jackson, K.; White, J. M.; Flynn, B. L. (J. Org. Chem., 2014)

(untitled) - Álvarez-Fernández, A.; Suárez-Rodriguez, T.; Suárez-Sobrino, Á. L. (J. Org. Chem., 2014)

(untitled) - Tymann, D.; Klüppel, A.; Hiller, W.; Hiersemann, M. (Org. Lett., 2014)

(untitled) - Nagaraju, C.; Prasad, K. R. (Angew. Chem., Int. Ed., 2014)

(untitled) - Hext, N. M.; Hansen, J.; Blake, A. J.; Hibbs, D. E.; Hursthouse, M. B.; Shishkin, O. V.; Mascal, M. (J. Org. Chem., 1998)

(untitled) - Jevric, M.; Zheng, T.; Meher, N. K.; Fettinger, J. C.; Mascal, M. (Angew. Chem., Int. Ed., 2011)

(untitled) - Li, Y.; Meng, Y.; Meng, X.; Li, Z. (Tetrahedron, 2011)

(untitled) - Ramakrishna, K.; Kaliappan, K. P. (Synlett, 2011)

(untitled) - McClure, C. K.; Kiessling, A. J.; Link, J. S. (Org. Lett., 2003)

(untitled) - Singh, V.; Sahu, B. C.; Mobin, S. M. (Synlett, 2008)

(untitled) - Bandaru, A.; Kaliappan, K. P. (Synlett, 2012)

(untitled) - Wilson, L. J.; Yang, C.; Murray, W. V. (Tetrahedron Lett., 2007)

(untitled) - Simonov, A. Y.; Bykov, E. E.; Lakatosh, S. A.; Luzikov, Y. N.; Korolev, A. M.; Reznikova, M. I.; Perobrazhenskaya, M. N. (Tetrahedron, 2014)

(untitled) - Torney, P.; Shirsat, R.; Tilve, S. (Synlett, 2014)

Macrocycles: Construction, Chemsitry and Nanotechnology Applications - Davis, F.; Higson, S. (John Wiley & Sons, 2011)

(untitled) - Kotha, S.; Manivannan, E.; Ganesh, T.; Sreenivasachary, N.; Deb, A. (Synlett, 1999)

(untitled) - Kotha, S.; Sreenivasachary, N. (Indian J. Chem., 2001)

(untitled) - Wybrow, R. A. J.; Edwards, A. S.; Stenvenson, N. G.; Adams, H.; Johnstone, C.; Harrity, J. P. A. (Tetrahedron, 2004)

(untitled) - Justus, J.; Beck, T.; Noltemeyer, M.; Fitjer, L. (Tetrahedron, 2009)

(untitled) - Meyer-Wilmes, I.; Gerke, R.; Fitjer, L. (Tetrahedron, 2009)

(untitled) - Widjaja, T.; Fitjer, L.; Meindl, K.; Herbst-Irmer, R. (Tetrahedron, 2008)

(untitled) - Kotha, S.; Srinivas, V.; Krishna, N. G. (Heterocycles, 2012)

(untitled) - Kotha, S.; Deb, A. C.; Kumar, R. V. (Bioorg. Med. Chem. Lett., 2005)

(untitled) - Kotha, S.; Chavan, A. S.; Mobin, S. M. (J. Org. Chem., 2012)

(untitled) - Kotha, S.; Dipak, M. K. (Tetrahedron, 2012)

(untitled) - D’yakonov, V. A.; Trapeznikova, O. A.; de Meijere, A.; Dzhemilev, U. M. (Chem. Rev., 2014)

(untitled) - Kotha, S.; Mandal, K. (Tetrahedron Lett., 2004)

(untitled) - Kotha, S.; Mandal, K.; Deb, A. C.; Banerjee, S. (Tetrahedron Lett., 2004)

(untitled) - Kotha, S.; Mandal, K. (Chem. – Asian J., 2009)

(untitled) - Mehta, G.; Srikrishna, A.; Reddy, A. V.; Nair, M. S. (Tetrahedron, 1981)

(untitled) - Mehta, G.; Kotha, S. R. (J. Org. Chem., 1985)

(untitled) - Bertz, S. H.; Cook, J. M.; Gawish, A.; Weiss, U. (Org. Synth., 1986)

(untitled) - Gupta, A. K.; Fu, X.; Snydert, J. P.; Cook, J. M. (Tetrahedron, 1991)

(untitled) - Fu, X.; Cook, J. M. (Aldrichimica Acta, 1992)

(untitled) - Kotha, S.; Sivakumar, R.; Damodharan, L.; Pattabhi, V. (Tetrahedron Lett., 2002)

(untitled) - Magnuson, S. R. (Tetrahedron, 1995)

The Way of Synthesis - Hudlicky, T.; Reed, J. W. (Wiley-VCH, 2007)

(untitled) - Gore, S.; Baskaran, S.; König, B. (Org. Lett., 2012)

(untitled) - Kotha, S.; Chinnam, A. K. (Synthesis, 2013)

(untitled) - Kotha, S.; Chinnam, A. K.; Tiwari, A. (Beilstein J. Org. Chem., 2013)

(untitled) - Mehta, G.; Prabhakar, C. (Indian J. Chem., 1995)

(untitled) - Kotha, S.; Ali, R.; Tiwari, A. (Synlett, 2013)

(untitled) - Kotha, S.; Ali, R. (Heterocycles, 2014)

(untitled) - Kotha, S.; Ali, R.; Chinnam, A. K. (Tetrahedron Lett., 2014)

(untitled) - Kotha, S.; Ali, R.; Tiwari, A. (Synthesis, 2014)

(untitled) - Wallace, D. J. (Tetrahedron Lett., 2003)